Investigating the Role of Physical and Digital Environment on Creating Active School with Respect to the Mediating Role of Social Environment - Rahim Ramezani Nezhad; Hamid Reza Gohar.rostami; Yasaman Sadat Asl Ahmadi (Pamukkale University, 2022)
Reform Document of Education (FRDE), creating active schools by relying on environmental potentialities is the goal with utmost significance; therefore, the present study aimed to explore the role that physical and digital environments play in achieving this objective. To this end, a descriptive-correlational design was utilized to probe the perception of teachers and physical education experts (n=302) sampled from a population including 892 personnel of the Education Department of Guilan. Data were obtained using a 5-point Likert scale, and 30 experts judged the face and content validity. The reliability and construct validity of the scale was checked and confirmed by Cronbach's alpha (α=.87) and exploratory-confirmatory factor analysis. Using SPSS 22 and PLS3 for data analysis, researchers found that physical, social, and digital factors effectively created an active school environment .31, .23, and .29 percent of the variances. Moreover, Social context as the mediating variable was correlated with physical and digital environment .30 and .34, respectively. Relying on the findings of this research trend, policymakers and managers can enrich the physical and digital environments of the schools and move towards accomplishing principle 6.6 of FRDE, which highlights the role of the social environment in an effective educational system.